PENGARUH PENGELOLAAN KELAS DAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA DI SD NEGERI PURWOSARI - Asi, Niluh Suni; Hariani, Ni Made Mega; Sudarsana, Wayan (JATMIKA : Journal Education and Learning of Elementary School, 2024)
This research aims to determine the influence of classroom management and the use of learning media on student learning motivation at Purwosari State Elementary School. The method used is quantitative, correlational in nature. Determining the sample in this study used the Stratified Sampling technique. Data collection techniques: observation, questionnaires and documentation. The data analysis technique used is simple regression testing and hypothesis testing.The research results show that classroom management partially has a significant effect on student learning motivation at Purwosari State Elementary School. The use of learning media partially has a significant effect on student learning motivation at Purwosari State Elementary School.